A Process Evaluation Of The Watauga County Drug Treatment Court - Shook, Angela Dawn (2009)
The current study is based on a process evaluation of the Watauga County drug treatment court and utilized in-person interviews with drug court team members in order to gain insight into program operations and procedures. Previous research on drug treatment courts is reviewed in order to examine strengths and weakness of drug court programs, qualitative research methods that are utilized to research drug treatment courts, and findings and methodologies of previous process evaluations. Descriptive data for active participants in the program are provided. In-depth analysis of interviews revealed six themes regarding program operations. Themes of participant eligibility, judicial supervision and participant accountability, access to treatment and social services, treatment and sanction strategies, team communication, and community support are explored in relation to previous research on drug treatment courts. Discussion of results emphasizes the potential impact of majorthemes on the effectiveness of the drug court program